2005
DOI: 10.1159/000084548
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Aspirin and Acetaminophen on Proinflammatory Cytokine-Induced Pain Behavior in Mice

Abstract: Aspirin (ASA) is a widely used oral analgesic which acts as an inhibitor of cyclooxygenase. Acetaminophen (ACET) is also an effective analgesic and may selectively inhibit brain prostaglandin synthetase. Various proinflammatory cytokines injected into the central nervous system show pain behavior. In the present study, the effects of orally administered ASA and ACET on pain behaviors induced by various proinflammatory cytokines were examined. At a dose of 100 mg/kg, ASA or ACET did not affect the pain behavior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 44 publications
(27 reference statements)
2
16
1
Order By: Relevance
“…Since aspirin has been reported to inhibit the function of TNF-α and IFN-γ 23 , we examined the effect of aspirin treatment on IFN-γ and TNF-α levels in BMMSC implants at 2–14 days after implantation. We showed that aspirin treatment reduced the levels of IFN-γ and TNF-α without affecting IL-10 level (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since aspirin has been reported to inhibit the function of TNF-α and IFN-γ 23 , we examined the effect of aspirin treatment on IFN-γ and TNF-α levels in BMMSC implants at 2–14 days after implantation. We showed that aspirin treatment reduced the levels of IFN-γ and TNF-α without affecting IL-10 level (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It inhibits osteoclastogenesis, and improves osteogenesis by affecting multiple biological pathways, such as inhibition of COX2, COX1, and PGE2 activity 15,23,39 . Epidemiological study suggests that aspirin may have a moderate beneficial effect on bone mineral density in postmenopausal woman 15 .…”
Section: Discussionmentioning
confidence: 99%
“…with glutamate (20 mg), substance P (SP) (0.7 mg), TNF-a (100 pg/5 ml), or IFN-g (100 pg/5 ml). The dose of glutamate, SP, and cytokines, which equally affected pain response, was determined by our previous studies (Choi et al 2003;Kwon et al 2005aKwon et al , 2005bPark et al 2010). …”
Section: Glutamate Substance P and Pro-inflammatory Cytokines-inducmentioning
confidence: 99%
“…Such a mechanism has been observed even with 100 mg daily doses of ASA, but some investigators suggest such an effect occurs with higher doses, 200-300 mg/day. (Goldstein et al, 2006;Ikonomidis et al, 1999;Kwon et al, 2005;von Känel et al, 2008). The effect is associated with inhibition by this substance of IkB kinase-b, with consequent inactivation of cytokine-inducing nuclear factor kappa b (NK-kb) (Yin et al, 1998).…”
Section: àmentioning
confidence: 99%